Galangin-Loaded Gold Nanoparticles: Molecular Mechanisms of Antiangiogenesis Properties in Breast Cancer - Malik H. Qaddoori; Hanady S. Al-Shmgani (International Journal of Breast Cancer)
Angiogenesis is important for tissue during normal physiological processes as well as in a number of diseases, including cancer. Drug resistance is one of the largest difficulties to antiangiogenesis therapy. Due to their lower cytotoxicity and stronger pharmacological advantage, phytochemical anticancer medications have a number of advantages over chemical chemotherapeutic drugs. In the current study, the effectiveness of AuNPs, AuNPs-GAL, and free galangin as an antiangiogenesis agent was evaluated. Different physicochemical and molecular approaches have been used including the characterization, cytotoxicity, scratch wound healing assay, and gene expression of VEGF and ERKI in MCF-7 and MDA-MB-231 human breast cancer cell line. Results obtained from MTT assay show cell growth reduction in a time- and dose-dependent aspect; also, in comparison to individual treatment, a synergistic impact was indicated. CAM assay results demonstrated galangin-gold nanoparticle capacity to suppress angiogenesis in chick embryo. Additionally, altering VEGF and ERKI gene expression was recorded. Taken together, all the results can conclude that galangin-conjugated gold nanoparticles can be a promising antiangiogenesis supplemental drug in breast cancer treatment.